Direct functionalization of Mn12-(methacrylate) clusters on Si(100): surface characterization and electrochemical properties - Ledezma Gairaud, Marisol (2016)
The reaction of H–terminated Si(100) with methacrylate–substituted manganese carboxylate clusters [Mn12O12{CH2C(CH3)COO}16(H2O)4], [Mn12–(methacrylate)] via hydrosilylation afforded Mn12–(methacrylate)−Si(100). The chemically modified surface was studied with an atomic force microscope (AFM), X–ray photoelectron spectra (XPS), a cyclic voltammeter (CV) and electrochemical impedance spectra (EIS). XPS show several Mn and Si electronic signatures that indicate the tailoring of Mn12–(methacrylate) on the surface. The CV plot of Mn12–(methacrylate)−Si(100) has two irreversible cathodic waves at −0.76 and −0.44 V, assigned to Mn(IV)/Mn(III) and Mn(III)/Mn(II) processes. The calculated charge at –0.44 V was 3.14 x 10–5 C cm–2. An equivalent-circuit model was proposed based on EIS data and element circuit analysis. EIS show that the electronic and structural features of Mn12–(methacrylate) on a surface greatly influence the electron transfer.